Paradoxical Relationship Between Glycated Hemoglobin and Longitudinal Change in Physical Functioning in Older Adults: A Prospective Cohort Study. (21st June 2018) - Wu, I-Chien; Hsu, Chih-Cheng; Chen, Ching-Yu; Chuang, Shu-Chun; Cheng, Chiu-Wen; Hsieh, Wan-Shan; Wu, Ming-Shiang; Liu, Yen-Tze; Liu, Yo-Hann; Tsai, Tsung-Lung; Lin, Cheng-Chih; Hsiung, Chao A
Abstract: Background: Hyperglycemia with high hemoglobin A1c (HbA1c ) levels is associated with significant health risks. However, the relationship between HbA1c levels and the physical functioning status in later life remains uncertain and so is the possible underlying mechanism. Methods: We conducted a prospective study of 2, 565 initially well-functioning community-dwelling older adult aged 55 years and older from the Healthy Aging Longitudinal Study in Taiwan. Each participant received baseline measurements of blood HbA1c and inflammatory markers levels and repeated assessments of physical functioning over a mean follow-up period of 5.3 years. We used generalized linear mixed-effects regression to estimate the adjusted changes in the odds ratio for self-reported physical functioning impairment and Short Physical Performance Battery (SPPB) score according to baseline HbA1c levels (categorized into 0.5% increments from <5.5% to ≥7.0%). Results: HbA1c levels showed a U-shaped relationship with changes in the odds ratio for physical functioning impairment and SPPB score ( p for quadratic term < .001). Compared with participants with an HbA1c of 5.5% to <6.0%, those with an HbA1c of <5.5% or ≥7.0% had a higher annual increase in the odds ratio for physical functioning impairment (odds ratio [95% confidence interval] per year, 1.25 [1.04–1.50] and 1.21 [1.04–1.41]) and a higher annualized decrease in SPPB score (coefficient [95% confidence interval], −0.05 [−0.10 to 0.00] and −0.04 [−0.08 to 0.00]). These relationships were nonlinear only in participants with high soluble interleukin-6 receptor levels (>48, 124 pg/mL; p for interaction < .05). Conclusions: High and low HbA1c levels at baseline are associated with faster physical functioning decline, particularly among individuals with elevated circulating soluble interleukin-6 receptor, a sign of enhanced interleukin-6 trans-signaling.